Effect of GA3 on Growth and Some Physiological Characterizes in Carrot Plant (Daucus Carota L.) - Abbas, E. D. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This experiment was carried out in the field of researches in Kalar Technical Institute / Field crop dept. The aim of the research is to study the effect of foliar sprays of different concentrations of Gibberellic acid on growth and some physiological characterizes in Carrot plant (local white cultivar). The experiment treatments included three concentrations of Gibberellic acid (0, 50 and 100 ppm) and were carried out as applicable agricultural project (3Ã—4). And the results were recorded as follows:                                                       In using the Gibberellic acid concentration at (50 ppm) led to increase significantly the studied characteristics particularly plant height cm, number of branch/ plant, number of flower/ plant, shoot fresh weight (gm), fresh weight of biological weight gm/plant, shoot dry weight (gm), dry weight of biological weight gm/plant, chlorophyll content (Âµg/cm2), when compared with the other concentrations levels and controlling plants. And GA3 decreases significantly some of the studied characteristics as root fresh weight (gm), root dry weight (gm) and soluble carbohydrate which that compared with the controlling plants.